English - Español, Español; Español, Español; Español, Español; Español, Español (Ars Pharmaceutica (Internet), 1991)
Three new guaianolides 11-H-13-rnethylsulfonylgrosheirnin 5 (Grosulfeirnin), 8-deoxy-11, 13-dihydroxygrosheimin 7 and 8-deoxy-11-hydroxy-13-chlorogrosheimin 8 have been isolated from the leaves of Cynara scolymus L. Besides, 8-epigrosheirnin 9 has been isolated for the ftrst time frorn this source. The structures were deterrnined by spectroscopical rnethods and by chernical correlations.